Using Mentoring as a Part of Professional Development - Alexa Lamm; Amy Harder (EDIS)
AEC-401, a 5-page fact sheet by Alexa Lamm and Amy Harder, defines mentoring, give a brief history, and reviews the stages of the mentoring process. It also highlights the benefits mentors, protégés, and organizations can expect from the utilization of a mentoring process. Published by the UF Department of Agricultural Education and Communication, December 2008.